Exploring Women’s Experiences of Amniocentesis: A Qualitative Content Analysis - Jaruwan Kownaklai; Umaporn Kuasit; Nanthiya Thaicharoen (Iranian Journal of Nursing and Midwifery Research)
Background: The decision and experience of high-risk pregnant women to undergo amniocentesis can depend on their setting, context, social structures, and significant others, including cultural values and beliefs. What is less understood is women’s experience with decision-making, which may contribute to their anxiety during and after amniocentesis. This study aimed to explore the decision-making experiences of Thai pregnant women undergoing amniocentesis. Materials and Methods: A qualitative content analysis approach was employed to collect and analyze data. Purposive sampling and in-depth interviews were conducted between July and October 2021 with 15 Thai high-risk pregnant women after undergoing amniocentesis. Data analysis involved multiple readings of transcriptions to discern themes and understanding of the women’s stories. Results: Four themes of decision-making experiences were identified: (1) “Shocked, worried, and questioned why the risk was high”; (2) “Does my baby have Down syndrome? I want to know”; (3) “Worried”; and (4) “Relief from anxiety.” Conclusions: Women’s experiences with amniocentesis involved uncertain positive and negative feelings through the journey of undergoing, waiting, and receiving the test results. The nurses and nurse-midwives played an important role in counseling Thai pregnant women about whether to undergo amniocentesis.